Psychophysiological Responses to a Brief Self-Compassion Exercise in Armed Forces Veterans - Gerdes, Samantha; Williams, Huw; Karl, Anke (Frontiers in Psychology, 2022)
Armed Forces personnel are exposed to traumatic experiences during their work therefore they are at risk of developing emotional difficulties such as post-traumatic stress disorder (PTSD), following traumatic experiences. Despite evidence to suggest that self-compassion is effective in reducing the symptoms of PTSD, and greater levels of self-compassion are associated with enhanced resilience, self-compassion in armed forces personnel and armed forces veterans (AFV) remains under-researched. As a result, it is not known if therapeutic approaches that use self-compassion interventions are a safe and effective treatment for this population. Therefore, the current study aimed to investigate whether a single self-compassion experimental induction temporarily reduced hyperarousal symptoms and increased feelings of social connectedness in AFV. The current study also investigated the association between PTSD symptom severity, emotion regulation and self-compassion in 56 AFV. All participants listened to a loving-kindness meditation for self-compassion (LKM-S) and psychophysiological recordings were taken throughout. Psychophysiological effects were observed including heart-rate (HR), skin conductance (SCL) and heart-rate variability (HRV), to determine associations with PTSD and changes in response associated with the self-compassion induction. PTSD symptom severity, dispositional emotion regulation and self-compassion were measured, and participants also completed state measures of hyperarousal and social connectedness before and after the LKM-S. The findings partially demonstrated that self-compassion can be elicited in an AFV population but there were considerable individual differences in psychophysiological responses. The findings are discussed in light of existing theories of PTSD and self-compassion and the implications of using self-compassion based psychological approaches with AFV.